Thermo-responsive electrospun scaffolds for enzymatic-free passage and mammalian cell phenotype support - Ruiter, Floor A.A. (2018)
Current conventional cell culture methods for the expansion of cells to large quantities for tissue engineering and regenerative medicine application relies on the use of enzymatic digestion passaging. However, this method significantly reduces the cell viability, due to the destruction of important cell-surface proteins and therefore considered undesirable for the subsequent cell therapies [1]. Research has led to the development of thermo-responsive surfaces for the continuous culture of cells. These thermo-responsive materials properties can be used to passage cells from the surface when the cell culture temperature is reduced. Conventional cell culture is performed on a 2D platform, however this can result in undesired de-differentiation, due to lack of similarities to the natural extracellular matrix (ECM) environment. This thesis aims to develop a thermo-responsive 3D fibre-based scaffold, fabricated by electrospinning, to create an enzymatic-free 3D cell culture platform for the expansion of mammalian cells with the desired phenotype for clinical use. In particular the expansion of human corneal stromal cells (hCSCs), which have been observed to de-differentiate to their active myofibroblastic phenotype with conventional 2D cell culture methods were examined here.